The Dynamics of Policy Implementation: Social Service Agency Strategies for the Social Transformation of Street Children (2023-2024) - Adila Puspa Hestiantini; Utami Nur; Dita Purnama (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes the dynamics of the implementation of the Street Children Development Program in Pontianak City during 2023–2024, a period marked by an increase in the number of street children from 29 to 37 individuals, along with the emergence of new issues such as drug and alcohol misuse. Employing a descriptive qualitative approach and drawing upon Edward III’s (1980) theoretical framework, the research examines four key variables of policy implementation: communication, resources, disposition, and bureaucratic structure. Data were collected through in-depth interviews with 15 informants, consisting of 8 representatives from the Social Affairs Office, 4 from the National Narcotics Agency (BNN), and 3 from the Indonesian Child Protection Commission (KPAI) of Pontianak City. The findings indicate that disposition particularly the attitudes and commitment of implementers serves as the primary driving variable that compensates for limitations in resources. Moral commitment and empathy among implementers emerge as critical enablers of successful program implementation. Meanwhile, resource constraints have stimulated adaptive innovations through collaborative strategies and resource pooling with partner institutions. The study demonstrates that in the context of social policy, human factors (disposition) can offset material constraints (resources), while communication through task forces and supportive bureaucratic structures creates an implementation ecosystem in which these variables reinforce one another despite limited resources. Overall, the findings reveal that implementer disposition functions as a compensatory mechanism for resource limitations, while cross-sectoral collaboration through task forces constitutes an effective strategy for fostering implementation synergy. The study recommends institutionalizing collaborative models, strengthening resource capacity, and enhancing bureaucratic flexibility to optimize the effectiveness of future street-children development programs.